Assessment of mean testicular volume in adolescent school boys of Udaipur district in 10 to 18 years at different stages of pubertal development - Babani, Tarun; Sareen, Devendra; Goyal, Dileep (International Journal of Contemporary Pediatrics, 2020)
Background: The most obvious and important changes during puberty are secondary sexual characters. To check the correlation between testicular volumes with secondary sexual characters, nutritional status in Udaipur schoolboy’s assessment of testicular volume by prayer orchidometer is easy and reliable and accurate method in community. Aim of the study was to find out mean testicular volume by prader orchidometer at different stages of pubertal development. Methods: Children between 10 to 18 years of age (525 in numbers) from schools of Udaipur city were included. Children thoroughly examined for presence of any systemic disorders or major surgery was excluded. Informed consent with parents was taken Testicular volume assessment done by praders orchidometer with Tanner staging and correlation was statically analysed. Results: Maximum boys belonged to 15-16 years of age group (14.7%), and minimum belongs to 10-11 years age group (9.3%). Secondary sexual characters increases as mean testicular volume increases. The mean testicular volume for P1 (4.46 ml) and P5 (22.68 ml) and G1 (4.69 ml) and G5 (23.27 ml) with a p<0.05. Conclusions: Testicular volume adds more objectivity in SMR detection and helps to differentiate early genital maturation than pubic hair. Study population had early rise of testicular volume before pubic hair clinically visible which shows that testicular volume is the first to increase with the onset of puberty.